Radial and axial-radial compressor elbow intake system - Antas, Stanisław (Advances in Mechanical and Materials Engineering, 2022)
The elbow is the exhaust system of the flow channel of the radial and axial-centrifugal compressor, in which the flow direction changes from radial to the direction determined by the diffuser axis of the combustion chamber. The paper presents a method of determining the parameters of the stream in the outlet cross-section of the exhaust system of a radial and axial-centrifugal compressor. The analysis covers the knee-type exhaust system. An appropriate method of determining the geometrical parameters for this type of exhaust duct is also presented. These methods can be used during the compressor conceptual design and are based on the energy conservation equation, the flow continuity equation, the first and second law of thermodynamics as well as gas-dynamic functions and definitions used in the theory of rotor machines. The final part of the work contains the principles of selecting the computational value of the compressor with a radial blade diffuser and conclusions.